Spirituality and religiosity in the context of drug abuse - Oliveira, Ana Lívia Castelo Branco de (2017)
Objective: to investigate the influence of spirituality/religiosity in the context of drug abuse. Methods: this is an integrative review, conducted on the databases Web of Science, Latin American and Caribbean Literature in Health Sciences and SCOPUS. The following descriptors were used in the Portuguese and English languages: drug users, spirituality, religion, drug abuse treatment centers and treatment outcome. Results: eight articles were analyzed, among which there was a prevalence of publications of the year 2015 and of quantitative studies. The studies approached mainly the prevention of drug abuse, the change of the user’s behavior and the religious/ spiritual confrontation. Conclusion: spirituality/religiosity seems to be a positive factor for drug users facing treatment, as well as in the protection against the abusive use of these psychoactive substances.